Cluster Analysis of Wheat (Triticum aestivum L.) Genotypes Based Upon Response to Terminal Heat Stress - Poudel, Ankur; Thapa, Dhruba Bahadur; Sapkota, Manoj (International Journal of Applied Sciences and Biotechnology, 2017)
High temperature stress adversely affects plant physiological processes; limiting plant growth and reducing grain yield. Heat stress is often encountered due to late sowing of wheat in winter. Fifty wheat genotypes were studied for days to maturity, thousand kernel weight, grain filling duration, grain filling rate, and SPAD reading in alpha lattice design at Agriculture and Forestry University at Rampur, Chitwan, Nepal with the objective to identify superior heat stress tolerant varieties after clustering them based on their response to heat stress. All the genotypes were clustered using reduction in thousand kernel weight, heat susceptibility index for thousand kernel weight, heat susceptibility index for grain filling duration, area under SPAD retreat curve, maturity duration under normal condition, maturity duration at late sown condition, grain filling rate under normal condition and grain filling rate at late sown condition as variables and dendogram was prepared. UPGMA revealed that these genotypes formed five distinct clusters. The resistant genotypes and susceptible genotypes formed different clusters. The member of cluster 3 was found to be tolerant to terminal heat stress where as members of cluster 2 were found most susceptible to terminal heat stress. From this study genotype BAJ #1/SUP152 was found most tolerant to terminal heat stress. The genotypes belonging to superior cluster could be considered very useful in developing heat tolerant variety and other breeding activities.Int. J. Appl. Sci. Biotechnol. Vol 5(2): 188-193